INTELLECTUAL MIGRATION: RUSSIAN AND WORLD TRENDS - Viktoria Yu. Ledeneva (Высшее образование в России)
The article discusses the migration processes in a particular segment – intellectual migration. Intellectual emigration flows are analyzed over the past 20 years. There is also considered a complex combination of reasons and motives of migration, as well as the demand for scientists and specialists in international markets of intellectual labor. The author gives suggestions and recommendations for the implementation of special policy and regulations for intellectual migration.